The relationship between social adjustment and homesickness among new santri - Ilham Surya; Sitti Murdiana; Andi Halima (Program Studi bimbingan Konseling PPs UNM Makassar, 2023)
This study aims to discover the relationship between social adjustment and homesickness among new santri. The subject of the study was santri in the tenth grade of Madrasah Aliyah As’adiyah Putra Sengkang in Wajo Regency. A total of 62 santri were selected using the simple random sampling technique. The instruments of the study were the homesickness scale and the social adjustment scale developed by the researchers. A correlation test with Kendall's tau-b was implemented to analyze the data. The analysis showed that there was a 0.000 level of significance and a -0.343 correlation coefficient. The results of the study showed that there is a moderate negative relationship between social adjustment and homesickness among new santri.